EFFECT OF QUALITY OF CSR DISCLOSURE ON FINANCIAL PERFORMANCE OF MINING COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Budi Santoso; Yosefa Sayekti; Agung Budi Sulistiyo (International Journal of Social Science and Business, 2017)
ABSTRACTThis research was conducted on mining companies listed in Indonesia Stock Exchange in 2012-2015, using qualitative measurement of CSR disclosure. This study aims to examine the effect of CSR disclosure quality on the financial performance of mining companies in BEI through web.IDX. Sampling method in this research is purposive sampling method 100 Mining company. The analyzes used include instrument test data (validity test, reliability test), multiple linear regression analysis, classical assumption test (normality test, multicolinearity test, heteroscedasticity test), and hypothesis test (F test, t test, coefficient of determination). Research Results The quality of CSR disclosure positively affects the accounting performance (ROA) of mining companies in BEI period 2012-2015.Keywords: Quality of CSR Disclosure, ROA